Etrolizumab as induction and maintenance therapy in patients with moderately to severely active Crohn's disease (BERGAMOT): a randomised, placebo-controlled, double-blind, phase 3 trial - Sandborn, William J.; Panés, Julian; Danese, Silvio; Sharafali, Zaineb; Hassanali, Azra; Jacob-Moffatt, Rhian; Eden, Christopher; Daperno, Marco; Valentine, John F.; Laharie, David; Baía, Carolina; Atreya, Raja; et al. (Lancet Gastroenterology and Hepatology, 2022)
Background: Etrolizumab is a gut-targeted anti-β7 monoclonal antibody targeting α4β7 and αEβ7 integrins. We aimed to compare the safety and efficacy of two doses of etrolizumab with placebo in patients with Crohn's disease. Methods: BERGAMOT was a randomised, placebo-controlled, double-blind, phase 3 study done at 326 treatment centres worldwide. We included patients aged 18–80 years with moderately to severely active Crohn's disease (Crohn's Disease Activity Index [CDAI] score of 220–480, and a mean daily stool frequency score of ≥6 or a mean daily stool frequency score of >3, and a mean daily abdominal pain score of >1, as well as the presence of active inflammation on screening ileocolonoscopy) who had intolerance, inadequate response, or no response to one or more of corticosteroids, immunosuppressants, or anti-TNF therapy within the past 5 years. BERGAMOT consisted of three induction cohorts (a placebo-controlled, double-blind exploratory cohort [cohort 1]; an active treatment cohort not containing a placebo control [cohort 2]; and a placebo-controlled, double-blind pivotal cohort [cohort 3]) and one maintenance cohort. In induction cohort 3, during the 14-week induction, patients were randomly assigned (2:3:3) to receive matched placebo, 105 mg etrolizumab subcutaneously every 4 weeks (at weeks 0, 4, 8, and 12) or 210 mg etrolizumab subcutaneously (at weeks 0, 2, 4, 8, and 12), stratified by concomitant treatment with oral corticosteroids, concomitant treatment with immunosuppressants, baseline disease activity, and previous exposure to anti-TNF therapy. To preserve masking, all patients received two injections at weeks 0, 4, 8, and 12 and one injection at week 2. Week 14 etrolizumab responders from all cohorts were re-randomly assigned (1:1) to receive 105 mg etrolizumab (etrolizumab maintenance group) or placebo (placebo maintenance group) every 4 weeks for 52 weeks; patients in the induction placebo group underwent a sham re-randomisation to preserve masking. During maintenance, randomisation was stratified by CDAI remission status, concomitant treatment with oral corticosteroids, induction dose regimen, and previous exposure to anti-TNF therapy. All participants and study site personnel were masked to treatment assignment for both induction and maintenance. Co-primary induction endpoints at week 14 (placebo vs 210 mg etrolizumab) were clinical remission (mean stool frequency ≤3 and mean abdominal pain ≤1, with no worsening) and endoscopic improvement (≥50% reduction in Simple Endoscopic Score for Crohn's Disease [SES-CD]). Co-primary maintenance endpoints at week 66 (placebo vs etrolizumab) were clinical remission and endoscopic improvement. Efficacy was analysed using a modified intention-to-treat (mITT) population, defined as all randomised patients who received at least one dose of study drug (induction) and as all patients re-randomised into maintenance who received at least one dose of study drug in the maintenance phase (maintenance). Safety analyses included all patients who received at least one dose of study drug. Maintenance safety analyses include all adverse events occurring in both induction and maintenance. This trial is registered with ClinicalTrials.gov, NCT02394028, and is closed to recruitment. Findings: Between March 20, 2015, and Sept 7, 2021, 385 patients (209 [54%] male and 326 [85%] white) were randomly assigned in induction cohort 3 to receive placebo (n=97), 105 mg etrolizumab (n=143), or 210 mg etrolizumab (n=145). 487 patients had a CDAI-70 response in any of the induction cohorts and were enrolled into the maintenance cohort, of whom 434 had a response to etrolizumab and were randomly assigned to placebo (n=217) or 105 mg etrolizumab (n=217). At week 14, 48 (33%) of 145 patients in the 210 mg induction etrolizumab group versus 28 (29%) of 96 patients in the placebo induction group were in clinical remission (adjusted treatment difference 3·8% [95% CI –8·3 to 15·3]; p=0·52), and 40 (27%) versus 21 (22%) showed endoscopic improvement (5·8% [–5·4 to 17·1]; p=0·32). At week 66, a significantly higher proportion of patients receiving etrolizumab than those receiving placebo had clinical remission (76 [35%] of 217 vs 52 [24%] of 217; adjusted treatment difference 11·3% [95% CI 2·7–19·7]; p=0·0088) and endoscopic improvement (51 [24%] vs 26 [12%]; 11·5% [4·1–18·8]; p=0·0026). Similar proportions of patients reported one or more adverse events during induction (95 [66%] of 143 in the 105 mg etrolizumab group, 85 [59%] of 145 in the 210 mg etrolizumab group, and 51 [53%] of 96 in the placebo group) and maintenance (189 [87%] of 217 in the etrolizumab group and 190 [88%] of 217 in the placebo group). During induction, the most common treatment-related adverse events were injection site erythema (six [4%] of 143 in the 105 mg etrolizumab group, four [3%] of 145 in the 210 mg etrolizumab group, and none of 96 in the placebo group), and arthralgia (two [1%], one [1%], and four [4%]). In the maintenance cohort, the most common treatment-related adverse events were injection site erythema (six [3%] of 217 in the etrolizumab group vs 14 [6%] of 217 in the placebo: group), arthralgia (five [2%] vs eight [4%]), and headache (five [2%] vs seven [3%]). The most common serious adverse event was exacerbation of Crohn's disease (14 [6%] of 217 patients taking placebo and four [2%] of 217 patients taking 105 mg etrolizumab in the maintenance cohort). Interpretation: A significantly higher proportion of patients with moderately to severely active Crohn's disease achieved clinical remission and endoscopic improvement with etrolizumab than placebo during maintenance, but not during induction. Funding: F Hoffmann-La Roche.
CRIS-Team Scopus Importer:2022-11-11